TP001/#1553 GOG-3043 (NCT04831580): a randomized non-inferiority trial of robotic versus open radical hysterectomy for early stage cervical cancer (ROCC). (4th December 2022) - Bixel, Kristin; Leitao, Mario; Chase, Dana; Quick, Allison; Lim, Peter; Eskander, Ramez; Gotlieb, Walter; Lococo, Salvatore; Martino, Martin; Mccormick, Colleen; Myers, Tashanna; Tewari, Krishnansu; et al.
Abstract : Objectives: Minimally invasive radical hysterectomy (MIRH) offers many perioperative advantages compared to the open approach. The Laparoscopic Approach to Cervical Cancer (LACC) trial, however, found that MIRH was associated with an increased risk of recurrence and death from disease. Subsequent studies suggest differences in outcomes are mitigated by avoidance of intrauterine manipulators and performance of protective vaginal closure prior to colpotomy. ROCC seeks to re-examine the oncologic safety of MIRH when performed with robotic assistance utilizing comprehensive tumor containment. Methods: ROCC is a multi-center prospective, randomized, non-inferiority trial. Patients with FIGO 2018 stage IA2-IB2 cervical cancer with squamous cell, adenocarcinoma, and adenosquamous carcinoma histology are eligible. Preoperative pelvic MRI confirming tumor size <4 cm without evidence of extracervical extension or metastases is required. No transcervical manipulators are allowed and tumor containment prior to colpotomy using pre-specified surgical techniques are mandatory. The primary objective is 3-year DFS. Secondary objectives include DSS, OS, patterns of recurrence, complications, patient reported outcome measures, and lymphedema. 420 patients will be enrolled in each arm which will provide 90% power to exclude an absolute decrease in DFS by 7% (HR <= 1.375) with a log-rank test for non-inferiority with a one-sided alpha of 0.05. Interim analysis for futility planned after 370/640 patients enrolled (correlates with estimated 11/32 events). 20 sites are activated/enrolling and 4 patients have been randomized at the time of submission. Results: Trial in progress: There are no available results at time of submission. Conclusions: Trial in progress: There are no available results at time of submission.